Expression of γ-IFN responsive genes in scavenger receptor over-expressing monocytes is associated with xanthomatosis - Grewal, Thomas; Boudreau, Mathieu; Roy, Madeleine; Chamberland, Ann; Lefebvre, Chantal; Lavigne, Jaques; Davignon, Jean; Minnich, Anne (Atherosclerosis, 1998)
We have recently described an inherited over-expression of the macrophage scavenger receptor (SR) in blood monocytes from members of a kindred, only two of whom displayed extensive xanthomatosis. Using mRNA differential display we demonstrated abnormally high expression of the signal transducer and activator of transcription (STAT1 α) in monocytes from the proband II-2. Expression of γ-interferon inducible protein 10 (IP-10), a STAT1 α-responsive gene and mediator of inflammatory response, was also abnormally expressed in the monocytes from II-2. Over-expression of both genes was restricted to monocytes from II-2 and was not observed in monocytes from the clinically unaffected family members, unlike that of SR. Gel retardation assays with THP-1 cell extracts identified γ-IFN inducible DNA binding activity to three potential STAT1 DNA binding elements in the human IP-10 promoter region from nucleotides −245 to −188. Taken together these results suggest that γ-interferon mediated cell activation is responsible for STAT1 α-induced transcription of the IP-10 gene in THP-1 macrophages as well as in monocytes from II-2. Analysis of monocytes from familial hypercholesterolemic (FH) subjects, who frequently develop xanthomatosis, revealed a significant number of subjects with elevated STAT1 α and IP-10 expression. Our data suggest that the inflammatory effects of γ-IFN signaling could play a role in foam cell formation and xanthomatosis.